Vertébrés du Miocène moyen de Amor (Leiria) - importance stratigraphique - Antunes, M. Telles (2008)
Some outcrops in the western part of Leiria's diapir yielded continental fossils in five points near Amor village (mammals, other vertebrata, and gastropoda). This is most significant as it is the first locality where miocene age could undoubtedly been ascribed to formations northwards the Iberian Central Chain and Nazare's accident. Mammalian fauna comprises 18 taxa. A new cricetid species, Fahlbuschia freudenthali n. sp. is described. This fauna allows to date fossil-bearing units from Upper Orleanian, MN5 mammal zone, that may be correlated to Upper Langhian marine stage. As the fauna is quite varied, it is possible to recognize the main characters of environment and of climatic conditions. It may probably be assumed that at the time the climate was of mediterranean type, generally warmer than today.